Analisis Belanja Daerah Pemerintah Provinsi Jambi - Fathiyah Fathiyah; Abdi Sukmana; Hamid Majid; Masnun Masnun (Universitas Batanghari, 2021)
The purpose of this research is to analyze the efficiency of regional spending in Jambi provincial government. The research method used is descriptive and the analytical tools used in this study are the ratio of spending variance, the ratio of expenditure harmony and the ratio of spending efficiency. The data used in this study is secondary data in the form of budget realization report on the regional financial report of Jambi provincial government for the period 2015 - 2019. The results of this study concluded that the efficiency of spending in Jambi province based on the ratio of spending variance showed an average result of 91.41 meaning that the realization is smaller than the budgeted amount with the preferred difference category (favourable variance), while in the ratio of expenditure harmony based on the ratio of operating expenditure to total expenditure over the last five years shows an average yield of 74.27% and the ratio of capital expenditure to total expenditure on average of 25.72% , meaning the proportion of operating expenditure allocation is greater than the proportion of capital expenditures, and the next based on the results of the calculation of the ratio of efficiency of expenditure obtained results of 91.41% with the category of efficient performance. This means that the Jambi Provincial Government is able to save and efficiently in conducting regional expenditure.